Holocene pedoenvironmental situations in the eastern Sierra Morena region (Andújar, Spain) - Granados, N; Espejo, J M Recio (Quaternary International, 2002)
Analysis of soils and vegetational changes during the Holocene period in the eastern Sierra Morena region (Spain) indicates that Mediterranean soils with argillaceous horizons have replaced leptosols. Genesis of regosols has favoured development of mesophytic species
Keywords: Holocene; Sierra Morena (voyant); Soil; vegetation changes